The predictive value of platelet to lymphocyte ratio for procedural complications and mid-term mortality in aortic stenosis patients who underwent a transcatheter aortic valve implantation - Rodi Tosu, Aydin; Cinar, Tufan; Guler, Arda; Kahraman, Serkan; Gurbak, Ismail (Annals of Medical Research, 2021)
None
Keywords: Trans-Aortic Valve Implantation; Platelet To Lymphocyte Ratio; Inflammation; Mortality; Stroke; Vascular Complication.